The Effect of Liquidity, Leverage, Firm Size, Ceo Duality, Political Connection on Financial Distress with Profitability as a Moderating Variable in Property & Real Estate Sector Companies Listed on the Indonesian Stock Exchange for the Period 2018-2022. - Saudicha , Maynanda Syafa; Kautsar, Achmad (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This study aims to determine the effect of liquidity,leverage, firm size, CEO duality, political connection on financial distresswith profitability as a moderating variable in properties & real estatesector companies listed on the Indonesia Stock Exchange for the period2018-2022.Design/methodology/approach: The type of data used is quantitativedata sourced from secondary data. The population in this study areproperties & real estate sector companies listed on the Indonesia StockExchange for the period 2018-2022. The technique used in this sampling ispurposive sampling and 24 companies were obtained as samples in thisstudy. The data were analyzed using logistic regression and moderatedregression analysis (MRA) using modprobe and calculated with SPSSVersion 27 software.Research Findings: The results showed that leverage proxied by debt toasset ratio and political connection has a significant and negative effect onfinancial distress. While liquidity (current ratio), firm size, CEO dualityhas no significant effect on financial distress and profitability proxied byreturn on assets is also unable to moderate the effect of liquidity (currentratio), leverage (debt to asset ratio), firm size, CEO duality, politicalconnection on financial distress. Therefore, properties & real estate sectorcompanies are expected to manage debt effectively and carefully assessrisks and finances. Properties & real estate sector companies must alsoensure that the sustainability of the relationship can be maintained in thelong term to avoid the risks that can arise from political changes to avoidfinancial distress.Keywords: CEO duality; Financial distress; Firm size; Leverage; Liquidity;Political connection; Profitability